KORXONA AXBOROT TIZIMLARINI QOʻLLAB-QUVVATLASHDA ITAUTSORSINGDAN FOYDALANISHNING ILMIY-USLUBIY ASOSLARI (Marketing Journal, 2026)
AbstractThis article analyzes the scientific and methodological foundations of using IToutsourcing in supporting enterprise information systems. In the context of digitaltransformation, ensuring the continuity, reliability, and security of information systemshas become a key factor in enterprise performance. The study examines the essence ofIT outsourcing, its main forms and implementation mechanisms, and evaluates itsimpact on economic efficiency, technical stability, and management processes. Theresults indicate that a properly selected IT outsourcing model optimizes operationalcosts, improves service quality, and enhances the speed of managerial decisionmaking. Practical recommendations are also proposed to mitigate organizational andinformation security risks.Keywords: information systems, IT outsourcing, enterprise management, digitaltechnologies, technical support, information security, service quality, economicefficiency.